Fonio millet genome unlocks African orphan crop diversity for agriculture in a changing climate - Abrouk, Michael; Ahmed, Hanin Ibrahim; Cubry, Philippe; Šimoníková, Denisa; Cauet, Stéphane; Pailles, Yveline; Bettgenhaeuser, Jan; Gapa, Liubov; Scarcelli, Nora; Couderc, Marie; Zekraoui, Leila; Kathiresan, Nagarajan; et al. (Nature communications, 2020)
Sustainable food production in the context of climate change necessitates diversification of agriculture and a more efficient utilization of plant genetic resources. Fonio millet (Digitaria exilis) is an orphan African cereal crop with a great potential for dryland agriculture. Here, we establish high-quality genomic resources to facilitate fonio improvement through molecular breeding. These include a chromosome-scale reference assembly and deep re-sequencing of 183 cultivated and wild Digitaria accessions, enabling insights into genetic diversity, population structure, and domestication. Fonio diversity is shaped by climatic, geographic, and ethnolinguistic factors. Two genes associated with seed size and shattering showed signatures of selection. Most known domestication genes from other cereal models however have not experienced strong selection in fonio, providing direct targets to rapidly improve this crop for agriculture in hot and dry environments.
Keywords: genom rostlinný; genetická variace; Domestication; Digitaria; Genetic Variation; zemědělství; selekce (genetika); Selection, Genetic; molekulární evoluce; Africa; Agriculture; Climate Change; Molecular Sequence Annotation; Afrika; domestikace; Species Specificity; klimatické změny; Genome, Plant; anotace sekvence; druhová specificita; Evolution, Molecular; jedlá semena; Edible Grain